Cena i jakość - preferencje Polaków na rynku dóbr FMCG - Stańko, Aneta (Price and Quality - Poles' Preferences on FMCG Market, 2006)
Low prices and high quality of goods are the main factors determining purchasing behavior on FMCG market in Poland. The shopping preferences are linked to household income, which influence also the food consumption level. Customers show most interest in those shops which compete with others via attractive prices. For 87% of Poles this is of decisive importance, or is at least important. In 2005 the largest group of Poles (45%) spent all, almost all, or most of the money set aside for ordinary shopping in self-service shops. The domination of small shops is closeness to home, pleasant staff and fresh products. The last attribute is particularly important in FMCG sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 339-344